WOUND HEALING OF PERIODONTAL AND ORAL TISSUES: PART II - PATHO-PHISIOLOGICAL CONDITIONS AND METABOLIC DISEASES. REVIEW - Maria-Alexandra Martu; George-Alexandru Maftei; Ionut Luchian; Cristina Popa; Ana-Maria Filioreanu; Diana Tatarciuc; Giorgio Nichitean; Loredana-Liliana Hurjui; Liliana-Georgeta Foia (Romanian Society of Oral Rehabilitation, 2020)
From a clinical perspective doctors rely on auspicious wound healing on a daily basis. Without a thorough understanding of this process success in treatment cannot be obtained. Thus it is of utmost importance that clinicians know and understand both the local, but more importantly, the systemic factors, which most of the time are not so apparent, which can affect and delay wound healing. The oral cavity hosts a plethora of tissues that serve various functions, and in this complex environment cells, bacteria, viruses, and fungi live in a subtly balanced ecosystem. It is this complexity of factors, both systemic and local, that offer the healing particularities and challenges of the oral cavity.